Konstruksi Makna Ṣalawāt dalam Surah al-Ahzab Ayat 56: Kajian atas Tafsir Rūḥ al-Bayān - M. Nashiruddin; Mardiah Abbas; Juli Julaiha P. (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The complexity of the meaning of ṣalawāt in Surah al-Ahzab: 56 gives rise to differences in interpretation between the normative, theological, and spiritual dimensions, thus demanding an approach capable of reaching layers of inner meaning in an integrative manner. This need underscores the relevance of Sufi interpretation in understanding the relationship among Allah, angels, and humans in the construction of ṣalawāt. The focus of this study is on analyzing the construction of the meaning of ṣalawāt in the Tafsīr Rūḥ al-Bayān by examining its semantic structure and underlying epistemological framework. A qualitative approach based on a literature review is used, employing the thematic interpretation method (mawḍūʻī) combined with the ishārī approach to uncover the symbolic and spiritual dimensions. The results of this study indicate a layered differentiation in the meaning of ṣalawāt, including transcendent praise of Allah, requests for mercy from the angels, and human spiritual praxis oriented towards self-purification. The semantic structure demonstrates the interrelationship between language, theology, and inner experience, while theological relations emphasize the Prophet’s position as the axis of spiritual mediation. The Sufi dimension leads to the internalization of ṣalawāt as a path to the soul’s perfection through awareness of the Divine presence in worship. The epistemology of interpretation in Rūḥ al-Bayān demonstrates the integration of external and internal meanings through directed spiritual intuition. The implications of this study advance tafsīr studies by offering an integrative framework that connects textual analysis, depth of meaning, and spiritual experience for understanding the verses of the Qur’an.